2015
DOI: 10.1080/07373937.2015.1040027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature on the microwave-assisted vacuum frying of potato chips

Abstract: The objective of this study was to investigate the effect of low temperature on the microwave-assisted vacuum frying of potato chips. A newly built in-house microwave-assisted frying machine was developed and used in this study. The effect of low temperature on the microwave-assisted vacuum frying of potato chips was investigated via comparing sample properties prepared with the frying temperature of 90℃, 95℃ and 100℃. The experience was taken at the same vacuum degree in every frying process. Parameters of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
2
Order By: Relevance
“…Therefore, microwave heating has become popular for frying (Gharachorloo, Ghavami, Mahdiani, & Azizinezhad, ). Many authors reported that inclusion of microwave in vacuum frying improves its physical, textural, and nutritional properties (Oztop, Sahin, & Sumnu, ; Su, Zhang, & Zhang, ; Su, Zhang, Zhang, Adhikari, & Yang, ; Su, Zhang, Zhang, Liu, & Bhandari, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microwave heating has become popular for frying (Gharachorloo, Ghavami, Mahdiani, & Azizinezhad, ). Many authors reported that inclusion of microwave in vacuum frying improves its physical, textural, and nutritional properties (Oztop, Sahin, & Sumnu, ; Su, Zhang, & Zhang, ; Su, Zhang, Zhang, Adhikari, & Yang, ; Su, Zhang, Zhang, Liu, & Bhandari, ).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted vacuum frying (MVF) is a specific process of VF in which microwave was used as the only heating unit (Su, Zhang, & Zhang, 2015). It has been used for the food processing, especially for fruits and vegetables (Quan, Zhang, Zhang, & Adhikari, 2014;Su, Zhang, Zhang, Liu, & Bhandari, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of microwave as a heating source in microwave‐assisted vacuum frying is a new frying process. The purpose of applying heat through microwave is to decrease the frying temperature, so the fried product with good quality attributes and less oil can be produced . This was substantiated by the recent study of Su et al who stated that microwave‐assisted vacuum frying decreased the oil uptake, retained natural color, and produced crispier chips with better cellular integrity or structure as compared to those fried under vacuum alone.…”
Section: Oil Uptake and Quality Attributesmentioning
confidence: 98%